2003
DOI: 10.1002/jemt.10371
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular membrane trafficking in bone resorbing osteoclasts

Abstract: There is ample evidence now that the two major events in bone resorption, namely dissolution of hydroxyapatite and degradation of the organic matrix, are performed by osteoclasts. The resorption cycle involves several specific cellular activities, where intracellular vesicular trafficking plays a crucial role. Although details of these processes started to open up only recently, it is clear that vesicular trafficking is needed in several specific steps of osteoclast functioning. Several plasma membrane domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 84 publications
1
63
1
1
Order By: Relevance
“…Assuming that bicarbonate is extruded into the forming enamel by the distal membranes, such concept requires that to maintain electro-neutrality protons are pumped away from the enamel compartment by a proton pump in the basolateral membranes (see for ion transporting epithelial cells: van Adelsberg et al, 1993)). Remarkably however, maturation stage ameloblasts express a proton pump in the apical membrane (Lin et al, 1994), identical to the one found in the boneresorbing osteoclasts (vacuolar H + -ATPase, (Mulari et al, 2003)). The location of this vacuolar H + -ATPase suggests paradoxically that the ameloblasts are secreting protons into the forming enamel instead of bicarbonate.…”
Section: Introductionmentioning
confidence: 70%
“…Assuming that bicarbonate is extruded into the forming enamel by the distal membranes, such concept requires that to maintain electro-neutrality protons are pumped away from the enamel compartment by a proton pump in the basolateral membranes (see for ion transporting epithelial cells: van Adelsberg et al, 1993)). Remarkably however, maturation stage ameloblasts express a proton pump in the apical membrane (Lin et al, 1994), identical to the one found in the boneresorbing osteoclasts (vacuolar H + -ATPase, (Mulari et al, 2003)). The location of this vacuolar H + -ATPase suggests paradoxically that the ameloblasts are secreting protons into the forming enamel instead of bicarbonate.…”
Section: Introductionmentioning
confidence: 70%
“…85 It is mainly controlled by the small GTPases of the Rab family (for a detailed review, see 86 ) and more particularly Rab7 which regulates the late stages of the endosomal pathway from the basolateral membrane to the ruffled border. 87 In resorbing osteoclasts, Rac1 and Rab7 colocalization and interaction at the vesicle fusion zone of the ruffled border suggest a possible role of Rac1 in the formation of this structure.…”
mentioning
confidence: 99%
“…The activated clastic cell present four different specialized membrane domains: the sealing zone and ruffled border that face the bone matrix, the basolateral domain and the functional secretory domain, which are not in contact with the bone matrix but with the extracellular fluid and other cells (Mulari et al, 2003). Fig.…”
Section: Anexomentioning
confidence: 99%
“…Regulation and balancing of intracellular pH during acid secretion is maintained by a HCO 3 − /Cl − exchanger located at the basolateral membrane. This structure transports the excess of intracellular HCO 3 − ions outside the cells thus, preventing intracellular alkalinization, while importing chloride ions inside the cell for secretion to the resorption lacuna (Mulari et al, 2003). Once the mineral is dissolved, the organic phase is exposed to proteolytic enzymes synthesized and secreted by the clastic cell into the resorbing lacuna.…”
Section: Anexomentioning
confidence: 99%
See 1 more Smart Citation